2011
DOI: 10.1111/j.1365-2966.2011.19998.x
|View full text |Cite
|
Sign up to set email alerts
|

On the observed - correlation in Sloan Digital Sky Survey QSO spectra

Abstract: This paper investigates the effect of differential aperture loss with Sloan Digital Sky Survey (SDSS) fibres and examines whether such selection bias would result in the observed correlation between rest‐frame absorption equivalent width of Mg ii absorbers, Wr(2796), and mean associated [O ii] luminosity, , in SDSS QSO spectra. We demonstrate based on a Monte Carlo simulation that the observed Wr(2796) versus correlation of Mg ii absorbers can be well reproduced, if all galaxies found in deep surveys possess … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 33 publications
1
22
0
Order By: Relevance
“…This is what one expects based on the known W2796 versus ρ anti-correlation. While what we observe is consistent with the trend presented by López & Chen (2012) the actual detection fraction we find is much less than their model prediction because of the high luminosity threshold (i.e., 0.3L ⋆ [O II] ) imposed in our study. Here, we also find, for a given luminosity threshold, the [O ii] detection rate in Mg ii systems is higher in the SDSS-DR7 spectra than in the SDSS-DR12 spectra (see Fig.…”
Section: Detection Probability Of Nebular Emission Lines In Strong Mgsupporting
confidence: 78%
See 2 more Smart Citations
“…This is what one expects based on the known W2796 versus ρ anti-correlation. While what we observe is consistent with the trend presented by López & Chen (2012) the actual detection fraction we find is much less than their model prediction because of the high luminosity threshold (i.e., 0.3L ⋆ [O II] ) imposed in our study. Here, we also find, for a given luminosity threshold, the [O ii] detection rate in Mg ii systems is higher in the SDSS-DR7 spectra than in the SDSS-DR12 spectra (see Fig.…”
Section: Detection Probability Of Nebular Emission Lines In Strong Mgsupporting
confidence: 78%
“…This is expected from the increasing projected area of fibre with z which leads to high probability for the line emitting regions to come inside the fibre. Interestingly, in an effort to model the effect of finite fibre size López & Chen (2012) have shown that the fraction of systems for which the absorbing galaxy will give rise to [O ii] emission in QSO spectra increases as a function of W2796 and will depend on the fibre size. They showed that the detection fraction increases from ∼50% for W2796> 1Å to ∼90% for W2796 > 3Å when no limiting flux condition is applied.…”
Section: Detection Probability Of Nebular Emission Lines In Strong Mgmentioning
confidence: 99%
See 1 more Smart Citation
“…While this correlation does not necessarily imply the presence of winds (see López & Chen 2012), Nestor et al (2011) observed an association between the most extreme absorbers and starburst galaxies. These authors further showed that galactic outflows are necessary to account for the large velocity spread.…”
Section: Spatial Configuration and Massmentioning
confidence: 99%
“…The authors find that the association between strong MgII and damped Lyman-α systems (DLAs) strengthens at higher redshifts, even though the overall taxonomy of these absorbers as defined in Churchill et al (2000) does not change. There is evidence that the redshift evolution in the number density of MgII absorbers follows the cosmic star formation rate (Zhu & Ménard 2012;Matejek & Simcoe 2012), though the A&A 552, A143 (2013) effects of observational bias may still play an important role (López & Chen 2012). Prochter et al (2006) compared the incidence of strong MgII absorbers in quasar sight-lines with those found in GRB afterglows.…”
Section: Introductionmentioning
confidence: 99%